2013
DOI: 10.1371/journal.pone.0074654
|View full text |Cite
|
Sign up to set email alerts
|

Tumor and Endothelial Cell-Derived Microvesicles Carry Distinct CEACAMs and Influence T-Cell Behavior

Abstract: Normal and malignant cells release a variety of different vesicles into their extracellular environment. The most prominent vesicles are the microvesicles (MVs, 100-1 000 nm in diameter), which are shed of the plasma membrane, and the exosomes (70-120 nm in diameter), derivates of the endosomal system. MVs have been associated with intercellular communication processes and transport numerous proteins, lipids and RNAs. As essential component of immune-escape mechanisms tumor-derived MVs suppress immune response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(37 citation statements)
references
References 44 publications
2
35
0
Order By: Relevance
“…Moreover, we observed that the expression percentage of some surface antigens in most EMPs tended to decrease in comparison with that of parental cells, indicating the trend for loss of surface antigens in EMPs from their parental cells. These observations are in accordance with recent studies showing a higher expression of certain surface antigens on parental cells than on MPs released from them, 23,24 which supports the notion that MPs might selectively inherit surface antigens as a special mechanism for conveying information from originating cells to derived MPs.…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, we observed that the expression percentage of some surface antigens in most EMPs tended to decrease in comparison with that of parental cells, indicating the trend for loss of surface antigens in EMPs from their parental cells. These observations are in accordance with recent studies showing a higher expression of certain surface antigens on parental cells than on MPs released from them, 23,24 which supports the notion that MPs might selectively inherit surface antigens as a special mechanism for conveying information from originating cells to derived MPs.…”
Section: Discussionsupporting
confidence: 92%
“…Microvesicles (MVs) are the plasma membrane-derived circular fragments shed from the surface of MSCs and other cell types or released from endosomal compartment (Camussi et al 2010;Muturi et al 2013;Ratajczak 2011). These structures harbor various cell-derived components including surface receptors and ligands, messenger RNAs (mRNAs), microRNAs, proteins, and even some organelles.…”
Section: Mscs-derived Microvesiclesmentioning
confidence: 99%
“…Therefore, these stressors and their effects on stem cells, particularly MSCs, must be identified to maintain MSCs pools or optimize their expansion protocols (Mansouri et al 2012;Tower 2012). In addition, for selective tissue regenerative medicine or preserving MSCs pool, application of some new target tissue-based strategies and modulation of the target tissues to secrete more specific chemokines to facilitate MSCs homing might be possible (Naderi-Meshkin et al 2014).…”
Section: Mscs-derived Microvesiclesmentioning
confidence: 99%
“…IHC and immunocytochemical (ICC) staining was performed according to standard protocols with some modifications (Klein et al, 2011;Muturi et al, 2013). Briefly, ICC cells were grown in glass dishes to appropriate densities, washed with 1· PBS, fixed with 4% formaldehyde in PBS for 20 min, rinsed twice with 1· PBS for 5 min, and blocked with 10% normal goat serum (AbD Serotec) at room temperature for 60 min.…”
Section: Histochemical Ihc and Immunocytochemical Stainingmentioning
confidence: 99%